Encapsulation method for CaCO3 nanoparticles - Dihayati, Y.; Abdul Raman, Abdul Aziz; Abdullah, E.C.; Leong, Y.C.; Harcharan, S. (2007)
In this study, a simple wet encapsulation method was used to coat the nano calcium carbonate particles at the temperature of 802°C. Stearic acid was used as the coating agent at 3, 6 and 9 wt. Analysis of SEM images indicates that agglomeration can be reduced significantly by using 3wt amount of SA. TGA analysis proved that the coated nanoparticles has the same stability with uncoated particles at temperature below 230°C. XRD peaks show that coating has no effect on crystallization and there was no phase change after coating. Lowest surface area of 22.9 m2/g was obtained from BET analysis when coating was done at 3wt SA. The DRIFT analysis also showed that it can be successfully used to investigate the change of molecules structure after coating. XPS data showed that the carbon surface element increased significantly with increasing amount of SA used for coating. © 2007 Asian Network for Scientific Information.